Electropolymerization of 4,4'-Methylenedianiline onto the Gold Electrode in Non-Aqueous Medium and Investigation of Electrochemical and Spectroelectrochemical Behaviours - Yilmaz, Ecir; Demir Mulazimoglu, Aysen (Asian Journal of Chemistry, 2012)
In this work, electrochemical and spectroelectrochemical behaviours of 4,4'-methylenedianiline have been studied by using cyclic voltammetry, electrochemical impedance spectroscopy and differential pulse voltammetry technique. In cyclic voltammetry surface characterization performed study, the grafting process of 4,4'-methylenedianiline on the electrode surface has been performed using 1 mM 4,4'-methylenedianiline solution in 100 mM tetrabutylammonium tetrafluoroborate in the range from 0.0 mV to +1600 mV potential range at 100 mV s-1 sweeping rate with 30 cycles. The surface characterization process has been carried out by using cyclic voltammetry and electrochemical impedance spectroscopy technique in both aqueous and non-aqueous media. Differential pulse voltammetry technique has been used to support the clear binding of molecule to the electrode surface. A polymerization mechanism for the binding process has also been suggested.